2013
DOI: 10.1186/1471-2369-14-42
|View full text |Cite
|
Sign up to set email alerts
|

The mineralocorticoid receptor antagonist eplerenone reduces renal interstitial fibrosis after long-term cyclosporine treatment in rat: antagonizing cyclosporine nephrotoxicity

Abstract: BackgroundChronic cyclosporine-(CsA)-mediated loss of kidney function is a major clinical problem in organ transplantation. We hypothesized that the mineralocorticoid receptor antagonist eplerenone (EPL) prevents chronic CsA-induced renal interstitial volume increase, tubule loss, and functional impairment in a rat model.MethodsSprague–Dawley rats received CsA alone (15 mg/kg/d p.o.), CsA and EPL (approximately 100 mg/kg/day p.o.) or vehicle (control) for 12 weeks. At 11 weeks, chronic indwelling arterial and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 22 publications
1
18
0
2
Order By: Relevance
“…Nielsen et al [25] studied the effect of eplerenone (∼100 mg PO daily) on renal interstitial fibrosis after prolonged cyclosporine (CsA) treatment in rats. In contrast to our results, their results indicated that eplerenone significantly lowered blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Nielsen et al [25] studied the effect of eplerenone (∼100 mg PO daily) on renal interstitial fibrosis after prolonged cyclosporine (CsA) treatment in rats. In contrast to our results, their results indicated that eplerenone significantly lowered blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…However, prolonged use of cyclosporine A can induce renal fibrosis. Thus, its clinical use is in part limited by its nephrotoxicity effect (3,59). The cyclosporine A model is good for studying interstitial fibrosis (23).…”
Section: Mercuric Chloride (Hgcl 2 )mentioning
confidence: 99%
“…These data allow considering MR as a novel potential therapeutic target for IR and NAFLD. Moreover, MR blockade has been shown to ameliorate experimental organ fibrosis in the heart , lung and kidney . If that beneficial effects also occurs in the liver then MR blockade would provide action on both metabolic and fibrogenic phenomena rendering this class of drugs potentially useful agents for NASH.…”
Section: Discussionmentioning
confidence: 99%